GENITAL CONDYLOMAS. PREVALENCE, ETIOLOGY, TREATMENT AND PREVENTION - L.K. Aslamazyan; L.S. Namazova; M.G. Galitskaya (Педиатрическая фармакология)
The article is dedicated to the papilloma virus infection. As it became known in October 2008, the nobel prize in the field of medicine and physiology this year is awarded to the German doctor of Harald Zur Hausen who has proved the role of the human papilloma virus as causative factor of the cervical carcinoma. This is epoch making discovery because of human papilloma virus is most frequent of sexually transmitted infections. The authors demonstrated the high HPV prevalence. One of the most frequent manifestations of this infection is in more details presented pointed condy loma, clinical course of the disease and differential diagnostics of its various forms. Considering treatment inefficiency, the authors convincingly demonstrate that the only opportunity available to keep a human from the illness development is a specific immune prevention.Key words: papillomavirus infection, pointed condylomas, precancers, prevention.